Content Design Recommendation for Digital Product of Public Aquarium Using QFD : (Case Study: SeaWorld Ancol, Indonesia) - Dumilah, Dewi Retno; Santoso, Sugeng (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Public aquariums as part of the tourism industry are ted by the pandemic conditions which have caused a decline in visits. Concerns are also still looming over whether there will be another closure policy or a change in consumer behavior in the future. Therefore, Public Aquarium had to change its products and services to adapt to the new habits. This study aims to give recommendation design content on digital products developed as an alternative product form offered to consumers. The research began with a customer survey, followed by an analysis with two levels of QFD involving interviews and discussions. As a result, customers expect digital products that encourage learning about aquatic animals that develop interactive and engaging content. Public aquariums can design educational and entertainment content to convey their collection products into information and interactive technical functions that add value to consumer interest in the content provided.